The benefits of implementing authentic-based multimedia learning in higher education institutions. - Harun, Jamalludin (Scientific Research Publishing (SCIRP), 2022)
Multimedia has become one of the most complex and diverse digital learning media for creating knowledge and enabling a sensory learning environment that helps students to learn better and integrate information. By emphasizing on real-world experiences, learning is intended to be applied to students’ thought process. However, learning while having fun cannot be isolated from the media, which makes it easy for students to access it. This implies that the media must be able to fulfil the demands of students’ progress. According to existing learning theories, authentic-based learning environments aid students in developing appropriate and effective understanding. Personal relevance for the students’ perspective, authentic-based learning environments are positioned within suitable educational settings and the notion of an authentic-based learning environment is based mostly on situated learning theory and may be described in terms of the task setting of student roles. Students are always engaged in learning when the education is creative, interactive, and challenging. Thus, multimedia learning can create an authentic learning environment. Instructions that are not created using multimedia theories may result in an unproductive learning environment. This study examined some of the advantages that students may by from employing authentic-based multimedia learning in higher education. Internet databases with relevant information, such as SCOPUS, ERIC, Springer, IEEE, Emerald, Science Direct, Web of Science, and Google were searched. Research on the literature acquired from web sources has demonstrated that authentic-based multimedia learning environments provide several benefits to students in higher education institutions. Students’ attention is sustained as skills are reinforced because they are more engaging, fascinating, and fun to use as well as the creation and deployment of technology to improve student learning outcomes and the review of student attrition and classroom engagement. This also enabled students to transmit multimedia content. To improve students’ academic performance, higher education institutions should implement authentic-based multimedia learning in teaching and learning settings.